2007
DOI: 10.1080/08860220701274959
|View full text |Cite
|
Sign up to set email alerts
|

Increased Body Mass Index Is Not a Reliable Marker of Good Nutrition in Hemodialysis Patients

Abstract: Objective. The aim of the study was to assess the body fat (BF) composition in hemodialysis (HD) patients using anthropometry and bioelectrical impedance analysis (BIA) and investigate relationships between BIA-determined BF composition and nutritional parameters in different weight groupings. Design. Cross-sectional study. Setting. A tertiary-care university hospital. Methods. 164 HD patients (M/F: 89/75, mean age: 48.4 ± 15.8 years, mean HD duration: 58.2 ± 42.6 months) were divided into three groups accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Several other studies have shown similarly lower BMI in MHD patients as compared with controls [14][15]. The results showed 73% normal weight, 21% overweight and 3% obese patients undergoing haemodialysis in comparison to 59% normal weight, 24% overweight and 17% obese individuals undergoing haemodialysis as reported by Torun and associates [16]. On the other hand, 3% of MHD patients had BMI less than 18.5kg/m 2 in contrast with none in the control group.…”
Section: Discussionsupporting
confidence: 47%
“…Several other studies have shown similarly lower BMI in MHD patients as compared with controls [14][15]. The results showed 73% normal weight, 21% overweight and 3% obese patients undergoing haemodialysis in comparison to 59% normal weight, 24% overweight and 17% obese individuals undergoing haemodialysis as reported by Torun and associates [16]. On the other hand, 3% of MHD patients had BMI less than 18.5kg/m 2 in contrast with none in the control group.…”
Section: Discussionsupporting
confidence: 47%
“…Dry weight is determined by nephrologists by clinical trial and error with the attendant pitfalls when used for analysis. We did not find an association between baseline dry weight and albumin or inflammatory markers [56,57]. We did not analyze inter-dialytic weight gain vs. albumin change in our study; others have observed a negative effect of lower interdialytic weight gain on nPCR, prealbumin, and dry weight in longitudinal analyses [57].…”
Section: Discussionmentioning
confidence: 79%
“…26 On the other hand, Gallar-Ruiz et al did not find significant differences in total protein, albumin, pre-albumin and haemoglobin serum levels between haemodialysis patients with BMI < and >25 kg/m 2 , 27 and Torun et al reported lower levels of albumin and BUN in obese patients with haemodialysis. 28 The possible underlying mechanisms of these discrepancies were not explained…”
Section: Discussionmentioning
confidence: 99%